2005
DOI: 10.1149/1.2039939
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Diffusion Studies of Cu∕(5 nm Ru)∕Si Structures

Abstract: In contrast to physical vapor deposition (PVD), the electrochemical deposition (ECD) process is dependent upon substrate resistivity. ECD of Cu on ultrathin Ru diffusion barriers remains a technological challenge due to large resistivity increase over a wide plating area. Results are presented from the comparative investigation of interfacial stability and Cu diffusion processes in PVD and ECD Cu∕(50.3emnm0.3emnormalRu)∕Si structures. Cu can be conformally electroplated onto (50.3emnm0.3emnormalRu)∕Si surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…This result is consistent with previous articles that a failure Cu/Ru/Si structure is induced by the formation of a less dense Ru 2 Si 3 interfacial layer. 12,15,24 The columnlike ruthenium silicide layer promotes Cu diffusion, causing massive Cu reactions with Si. 13 In comparison, the Ru-B-C layer was superior to Ru in preventing Cu diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with previous articles that a failure Cu/Ru/Si structure is induced by the formation of a less dense Ru 2 Si 3 interfacial layer. 12,15,24 The columnlike ruthenium silicide layer promotes Cu diffusion, causing massive Cu reactions with Si. 13 In comparison, the Ru-B-C layer was superior to Ru in preventing Cu diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…2a͒ at 600°C indicate that Ru 2 Si 3 forms before Cu silicide. Other articles 12,15,24 have also indicated that the failure mechanism of a Cu/Ru/Si structure is related to Ru 2 Si 3 crystallite formation, which forms a discontinuous and less dense interlayer and causes massive Cu diffusion through these rapid diffusion paths. 13 In contrast, the GIXRD patterns in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable interest at the present time [1][2][3][4][5][6][7][8][9][10][11][12][13] in the possible use of ruthenium as an ultrathin trench liner in damascene copper plating which is currently employed in the microelectronics area for the production of on-chip interconnects. The advantages of ruthenium as a trench liner are that ideally it prevents copper transport from the filled trench into the silicon (thus averting device degradation), it is directly platable (dispensing with the need for a seed layer) and it provides strong adhesion between the electrodeposited copper and the barrier film (which reduces copper electromigration at the Ru/Cu interface).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among these steps, the diffusion barrier and Cu seed layer are formed by physical vapor deposition (PVD). Generally, metals deposited by the PVD method show good adhesion with the substrate and superior film properties, such as low resistivity and low surface roughness.…”
mentioning
confidence: 99%